Sürdürülebilir Mimarlıkta sakin Şehir (cıttaslow) Yaklaşımı - Aydoğan, Selma (Fen Bilimleri Enstitüsü, 2015)
Küreselleşme, Sanayi Devrimi ve modernizmin getirdiği olumsuz durumlara karşı ortaya çıkan yavaş hareketinin sonucu olarak sakin şehir kavramı ve sürdürülebilir mimarlık konularının birlikte değerlendirilmesi bu tezin konusunu oluşturmaktadır.  Sürdürülebilir mimarlık konusunun kapsamlı gereklilikleri, küresel sorunlarla birlikte çözüm arayışları ve sakin şehir kavramının sahip olduğu kriterlerin pratikteki sürdürülebilir potansiyeli, bu çalışmadaki temel unsurları oluşturmaktadır. Sakin şehirlerin uygulaması gereken kriterler ve sürdürülebilir mimarlık stratejilerinin paralelliği birlikte ele alındığında sürdürülebilir bir gelecekten söz etmek mümkün olabilmektedir.  Tez çalışmasında; Dünya’daki ve Türkiye’deki sakin şehirler; sakin şehir kriterlerini gerçekleştirmek için mevcut durumları ve projeleri ile birlikte ele alınmış, sürdürülebilir mimarlık ve kent kavramları ile birlikte değerlendirilmiştir. Tezin birinci bölümünde; sürdürülebilir mimarlık kavramı ve sakin şehir hareketi ile ilgili genel bilgiler verilmiş, çalışmanın amacı ve çalışmada izlenen yöntemler belirtilmiştir. İkinci bölümde; sürdürülebilir mimarlık kavramının geçmişten günümüze farklı aşamalardaki durumu ve tanımları yapılmış, sürdürülebilirlik kavramı çok yönlü ele alınmış; sürdürülebilir kalkınma kavramının şehirlere ve mimariye etkisi araştırılmıştır. Sanayi Devrimi ve küreselleşmenin etkisiyle yenidünya düzeni ve onun ekonomik etkilerinin mimarlık kavramına ve kent çehrelerine olan etkileri değerlendirilmiştir.  Çevre sorunları, doğa felaketleri ve enerji politikalarının olumsuz sonuçları çevre, enerji ve mimarlık konularının birlikte irdelenmesiyle organik mimarlık kavramını ortaya çıkarmıştır. Organik mimarlık kavramı çevresel tasarım, yeşil tasarım, ekolojik tasarım gibi kavramlarla devam etmiş, güneş mimarisi ve yeşil mimari olarak adlandırıldıktan sonra da en geniş anlamıyla ‘sürdürülebilir mimarlık’ olarak günümüze kadar ulaşmıştır. Enerji sorunu ve politikaları günümüz dünyasının ve mimarlığın yılardır en büyük problematiği haline gelirken, BM zirvelerinde ve uluslararası birçok platformda ele alınmıştır. Sürdürülebilir kalkınma modellerinin şehirlerdeki etkisinin önemi vurgulanmıştır. Tezin ikinci bölümünün sonunda ise alternatif sürdürülebilir bir kent modeli olarak sakin şehir kavramı önerilmiştir. Üçüncü bölümde; yavaş hareketi ve sakin şehir kavramının gelişimi, sakin şehir bileşenleri ve sakin şehir organizasyon yapısı ele alınmış, sakin şehir üyelik kriterleri başlıklar altında incelenmiştir. Yavaş hareketinin bir sonucu ve modern dünyanın hızlı yemek kültürüne eleştirel bir bakış açısı olarak yavaş yemek akımı ortaya çıkmıştır. Yavaş yemek akımının bütün kültürleri ve yaşam biçimlerini etkilemesiyle büyüyen hareket, Sakin Şehir (Cittaslow) kavramının doğmasını sağlamıştır. Sakin şehir kavramı; çevreye duyarlı yaklaşımı, kent yaşamı kalitesini iyileştirmeyi amaçlayan yapısı, yenilenebilir enerji kullanımını savunan, yerel üretimi / üreticiyi teşvik eden sürdürülebilir ekonomik yapısı ve toplumsal mekanizmaları olumlu anlamda etkilemesi nedeniyle büyüyerek, sürdürülebilir mimariye fayda sağlayacak alternatif bir kent modeli haline dönüşmüştür. Sakin şehir felsefesi kriterleri ile birlikte ele alınmıştır.  Dördüncü bölümde; Dünya ve Türkiye’deki sakin şehirlerin kriterleri ne ölçüde ve hangi nitelikte değerlendirdiği detaylı olarak incelenmiştir. Sakin şehirlerin kriterlerini sağlayabilmek için hazırladığı projeler, kent yaşamını ve kalitesini mimari bağlamda iyileştirme çabaları, çevresel konuları şehir ölçeğinde ele alma çabaları, enerji politikaları ve sosyal anlamda sürdürülebilirliği sağlamak için gerçekleştirilen kalkınma politikaları değerlendirilmiştir. Her şehrin kendi potansiyeline göre kriterlere farklı yorumlar getirdikleri ve bunun şehirler üzerindeki olumlu etkileri gözlemlenmiştir. Örneğin yenilenebilir enerji kullanımına çok önem veren Sebastopol, Amerika’nın en çok yenilenebilir enerji kullanan şehri olurken, sosyal sürdürülebilirliğe ağırlık veren Waldkirch (Almanya) kenti sürdürülebilir kalkınma konusunda Almanya’da pilot şehir seçilmiştir. Doğal rezervlerini korumayı çok iyi sağlayan San Vincenzo (İtalya) ve Katoomba (Avustralya), turizmde kalkınma sağlayarak gelişmiştir. Türkiye’deki çoğu sakin şehir, altyapı ve kent politikalarını geliştirmeye ihtiyaç duyarken, sürdürülebilir kalkınmanın temelini oluşturan yerel üretim konusunda olumlu değerlere sahiptir. Çalışmanın sonuç kısmında ise; tez çalışmasında elde edilen sonuçlara göre, genel bir değerlendirme yapılmış ve önerilerde bulunulmuştur. Bu değerlendirme ve önerilerle, sürdürülebilir mimarlık kavramının, sakin şehir felsefesinin sahip olduğu kentsel yaşam göstergeleri ile paralellik gösterdiği ve sakin şehir kriterlerinin kente doğru entegre edilmesiyle kentlerde yerel bir sürdürülebilir kalkınma modeli haline dönüşebileceği gözlemlenmiştir.

This thesis examines and interprets the position of a slow city, or “Cittaslow”, within sustainable architecture that was caused by the negative effects of globalization, Industrial Revolution and modernism.  Interpreting the position of a “Cittaslow” within sustainable architecture, is the main topic of this thesis. Slow movement, which started on the other side of the negative effects of globalization, Industrial Revolution and modernism, helped slow cities to be developed. The general principles of this study are the extensive necessities of sustainable architecture, investigating contingent solutions for global problems and the practical examination of sustainable potential of “Cittaslow” principles. This study will also consider the basic “Cittaslow” criteria in connection with the strategies of sustainable architecture in order to achieve a viable future.  “Cittaslow” in Turkey as well as around the World, are evaluated based on projects, the senses of each city and taking into account the current situations of sustainable architecture. These projects are discussed to potential of city by local municipality. In Turkey, municipality approaches can be distinctive at being a Cittaslow. Some municipality approaches have negative effects in a positive way, some municipality approaches turn into positive effects from a negative situation. This thesis examines all the above in four parts. The first part examines the basic information of sustainable architecture, the “Cittaslow” movement and the aim and methodology of the study as a whole.  The second part defines and analyzes sustainable architecture throughout times, processes sustainability, as a term, in various approaches, examines its effects in cities and in architecture in general. This section also investigates the economic effects of the Industrial Revolution and globalization in urban architecture. Environmental issues, natural disasters, negative effects of energy policies has caused environment, energy and architecture need to be considered all in one and this was indicating new, many-sided design discipline which has been termed as environmental design, green design, ecological design, organic architecture, solar architecture and green architecture in time. At the end, it has placed as sustainable which has the most extensive meaning.   Organic Architecture definition firstly is used by F. Lloyd Wright and has been developed by architects. UN and so many environmental group assemble and discuss about World, its environmental issues since 1970s and then sustainable architecture has become issue that is more important. Sustainable architecture is a complex issue that can be considered in many ways. Strategies of sustainable architecture are explained in detail at this part. These strategies make a definition not only about architecture but also about a sustainable life style. Strategies of sustainable architecture are categorized at six sections. These sections are about sustainable site and land use, sustainable community life, health and well-being, building materials, energy and water issues. These topics have been examined in detail at this part. Nowadays, global energy crisis has became such a great problem, that is often discussed in UN summit meetings where the importance of sustainable development methods in cities is emphasized. Energy using and urban policies become more important for city living and city quality. Thus city models are considered at this perspective. The most sustainable city model is “self-contained cities” which is close to alternative city model. At the end of the second part of the thesis, “Cittaslow” concept, as a related sustainable city method, is recommended.  The third part analyses the process of a “Cittaslow” concept throughout time, its components and organizational structure and the criteria needed for a city to be considered as one. Slow city organization includes a distribution of tasks which consider about different department subjects. These subjects includes slow city management commissions, slow city regulation rules, slow city membership and membership criteria. Within the slow movement and against the fast food culture, the slow food movement has also appeared. When a fast food restaurant was opened in Italy’s historical city center, there was a great protest. After these protest the importance of slow food increased and turned into a Slow Food Movement. It has been affected by contemporary lifestyle and various subcultures which in their turn leaded to the appearance of the “Cittaslow” movement. The “Cittaslow” concept, with its environmental conscious approach, with “aiming for better life” conditions, proposing alternatives for sustainable energy, promoting incentive economic structure for local productions and local producers and with its positive effects on social mechanisms, has become an ideal alternative city model for sustainable architecture. To be a member of Cittaslow requires having some properties. For example, slow city population must be under fifty thousand. Also so many policies must be provided by slow city municipalities. This requirements of excellence concept consist of 7 parts and 71 criteria. First part is about energy and environmental policy, second part is about infrastructure policies, third part is about quality of urban life policies, fourth part is about agricultural, touristic and artisan policies, fifth part is about policy for hospitality, awareness and training, sixth part is about social cohesion and seventh, also final part, is about partnerships. The fourth part evaluates, through various criteria and perspectives, “Cittaslow” in Turkey as well as around the World. It also determines “Cittaslow” criteria as developing applications for better life quality in cities in an architecture context, handling environmental issues on a city scale and energy policies and improvements for the sustainable energy. Study observations reveal that in fact every city interpret the criteria needed in various ways.  For instance, Sebastopol (USA) meets the criteria regarding renewable energy resources, Waldkirch (Germany) meets the criteria regarding its social sustainability and cities as Vincenzo (Italya) and Katoomba (Australia) meets the criteria regarding the preservation of their natural resources. Although most “Cittaslow” in Turkey needing improvements in substructure and city policies, they have encouraging signs for sustainable developments.  In Turkey, meeting with criteria and providing method of strategies must be more effective, prudential and includes radical solutions as World city cases. First slow city Seferihisar has the best criteria points in Turkey. Taraklı and Yalvac have restoration projects with good quality. Gökceada has second best point after Seferihisar. Yenipazar need projects about criteria to advance more. Halfeti is above average at providing criteria. All slow cities on Turkey needs more qualified approaches at infrastructure and urban life policies. Local production issues are at good levels in all slow cities in Turkey. Particularly in Turkey, using renewable energy sources must increase and be encouraged by governments. Sustainable strategies at building design and construction are necessity in terms of sustainable architecture. New building and city parameters must be considered in a sustainable way. Thus more environmentally friendly solution will be reached by energy conservation providing. The fifth and final part, appraise this study’s results and provides suggestions. Throughout these evaluations and suggestions, it is observed that sustainable architecture and Cittaslow movement are parallel to each other regarding to urban life indicators. Additionally, it is regarded that with integrating the criterias of cittaslow to the cities, Cittaslow movement can be implemented as a local, sustainable city development model. Thus sustainable architecture concept might be planned to be implemented with true urban policies at long term and the presence of environmentally sensitive public awareness.
An Approach To Slow City (cittaslow) in Sustainable Architecture
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: sürdürülebilir mimarlık; sakin şehir; sakin şehir hareketi; yavaş yemek; yavaş hareketi; yavaş yemek hareketi; sustainable architecture; slow city; slow movement; slow food; cittaslow